Deprescribing vitamin B6 in a Singapore community hospital - Alvin Shao Qiang Ong; Keith Zhong Hui Lee; Yee Shiang Wong; Eng Fui Lim; Dalvin Wan Hong Koh; Hui Yun Soh; Tsui Pik Chan; Gabriel Gerald Wenjun Yee; Yu Xian Loo; Cheryl Yan Fang Tan (BMJ Open Quality)
Introduction Vitamin B6 is commonly prescribed in hospitals in Singapore, although the clinical benefits are unclear. The Singapore Health Science Authority released a safety alert on high-dose vitamin B6 and the risk of peripheral neuropathy in May 2023.Methods Patient case notes were reviewed at the beginning of the project, revealing that vitamin B6 was successfully deprescribed in 15.2% of eligible patients at our hospital.We used a swimlane diagram to map processes and cause-and-effect diagrams to identify root causes. We brainstormed for interventions using 72 change concepts, aiming to streamline medication management practices for deprescribing vitamin B6.Results The percentage of patients with successfully deprescribed vitamin B6 increased from 15.2% to 100% during the project period. This corresponded to an 84.8% improvement. The additional 22 patients who had vitamin B6 deprescribed amounted to cost-savings of 1686 Singapore Dollars (SGD) per year. The projected savings over 1 year based on the current rate of deprescribing can be estimated to be SGD 13 567 per year. Furthermore, the new protocol that helped identify suitable patients for deprescribing has also led to positive feedback from the medical and pharmacy teams.Conclusion In conclusion, this project facilitated a significant increase in the percentage of patients with successful vitamin B6 deprescription, reducing patients’ pill burden, side effects and medication costs. It also resulted in a new protocol guideline for our healthcare teams to consider vitamin B6 deprescription in suitable patients.